2002
DOI: 10.1002/nbm.758
|View full text |Cite
|
Sign up to set email alerts
|

31P NMR spectroscopy of blood plasma: determination and quantification of phospholipid classes in patients with renal cell carcinoma

Abstract: Advanced renal cell carcinoma (RCC) has a poor prognosis and is characterized by an unpredictable clinical course. The aim of this study was to assess the systemic phospholipid distribution as a possible marker of tumor stage and tumor spread beyond the kidney. To this end, the effect of renal cell carcinoma (RCC) on phospholipid concentrations in blood plasma using 31P NMR spectroscopy was studied in: (a) 29 patients with RCC prior to nephrectomy; (b) 19 healthy volunteers; (c) three patients with other renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
48
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 34 publications
11
48
1
Order By: Relevance
“…This has also been observed in other tumor cells (Jantscheff et al, unpublished data) and this effect can be discussed as one possible cause for the strongly reduced LysoPC plasma amounts observed in patients with advanced metastatic cancer (17)(18)(19)(20)(21). In addition, a radical shift in tumor cell membrane FA composition toward saturated FAs was observed, culminating between 48 and 72 hours without increasing after further LysoPC exposure (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This has also been observed in other tumor cells (Jantscheff et al, unpublished data) and this effect can be discussed as one possible cause for the strongly reduced LysoPC plasma amounts observed in patients with advanced metastatic cancer (17)(18)(19)(20)(21). In addition, a radical shift in tumor cell membrane FA composition toward saturated FAs was observed, culminating between 48 and 72 hours without increasing after further LysoPC exposure (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…The inhibitory effects of LysoPC on B16.F10 cell adhesion were observed after approximately 48 to 72 hours at a threshold concentration of 400 mmol/L or greater, slightly higher than physiologic human plasma levels (200-400 mmol/L; refs. [16][17][18], and were remarkably intensified by repeated application of LysoPC. Because exposure to LysoPC concentration above the threshold did not alter expression levels of VLA-4 and P-selectin or binding to soluble structures (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPCs act as a bioactive mediator in various biological processes, including injury and inflammatory responses (29,30), cellular motility, growth and regulation of differentiation (31). Numerous clinical experiments have shown that serum LPCs levels are lower in patients with advanced cancer (32)(33)(34). However, the results of the present study also showed that LPCs containing saturated fatty acids were upregulated in CRC patients.…”
Section: Discussioncontrasting
confidence: 39%